B4 Detection of the aberrantly spliced exon 1 – intron 1 htt mRNA in HD patient post mortem brain tissue and fibroblast lines. (13th September 2016) - Bates, Gillian P; Osborne, Georgiana F; Ali, Nadira; Benjamin, Agnesska C; Papadopoulou, Aikaterini S; Howland, David; Tabrizi, Sarah J; Faull, Richard LM; Myers, Richard H; Landles, Christian; Neueder, Andreas
Abstract : Background: We have previously shown that exon 1 of the huntingtin gene does not always splice to exon 2 resulting in the production of a small polyadenylated mRNA that encodes the highly pathogenic exon 1 HTT protein. The level of this read-through product is proportional to CAG repeat length and present in all knock-in mouse models of HD (with CAG ≥ 50), utilising cryptic polyadenylation sites located at 677 bp and 1145 bp into mouse intron 1. The read-through product is also readily detected in the YAC128 and BACHD mouse models which both use a cryptic polyadenylation site that is located 7327 bp into human intron 1. However, the presence of this small exon 1 – intron 1 mRNA was not easy to detect in HD patient tissues using the assays that we initially developed. Aims: To develop novel quantitative RT-PCR assays to detect the exon 1 – intron 1 HTT mRNA in tissues from HD patients. Methods: We have now established a set of qPCR assays that quantify sequences located close to the cryptic polyadenylation site in human HTT intron 1. These have been applied to a series of fibroblast lines and post-mortem brain samples from individuals with either adult-onset or juvenile-onset HD. Results: The exon 1 – intron 1 HTT mRNA can be readily detected in the somatosensory cortex, hippocampus and cerebellum of post mortem brains from individuals with HD, particularly in those with early onset disease. These human HTT intronic sequences are also present in fibroblasts from juvenile HD patients. We shall also present data on changes in the relative abundance of the exon 1 – intron 1 Htt mRNA in a knock-in mouse model with disease progression. Conclusion: The highly pathogenic exon 1 HTT protein is generated in the tissues of people with HD through the aberrant splicing of HTT. Funding: Medical Research Council and CHDI Foundation